The correlation between traditional Chinese medicine constitution and prediabetes: a systematic review and meta-analysis - Chen, Liqian; Wang, Yun; Xie, Xinhui; Zhou, Zhiyi; Xie, Lu; Cai, Jiaxin; Li, Hao; Zhang, Xinyu; Ke, Yijin; Li, Qingzi; Wu, Zhiqi; Zhao, Xiaoshan; et al. (Frontiers in Endocrinology, 2026)
ObjectivesThe aims of this study were to investigate the distribution of traditional Chinese medicine (TCM) constitution types in individuals with prediabetes and to identify high-risk constitutions, thereby providing an evidence-based foundation for the prevention and treatment of prediabetes.MethodsWe systematically searched PubMed, Embase, Web of Science, the Cochrane Library, and four Chinese databases for literature examining the association between prediabetes and TCM constitution types. A single-proportion meta-analysis of cross-sectional studies and a comparative meta-analysis of case–control studies comparing individuals with prediabetes and the general population were performed using the Stata17.0 software. Effect sizes were expressed as odds ratios (ORs) with 95% confidence intervals (CIs). Study quality was assessed independently by two reviewers. The primary outcomes included the distribution of TCM constitution types in the prediabetes population and the comparative ORs between groups.ResultsA total of 30 cross-sectional studies and 5 case–control studies, involving 8,469 participants, were included. Among individuals with prediabetes, the pooled prevalence rates of phlegm-dampness constitution (PDC), balanced constitution (BC), yin-deficiency constitution (YIDC), qi-deficiency constitution (QDC), and damp-heat constitution (DHC) were 20% (95% CI: 16%–24%), BC 16% (10%–22%), 12% (10%–15%), 11% (9%–14%), and 10% (7%–13%), respectively. Meta-analysis of case–control studies indicated that the ORs for prediabetes risk in individuals with PDC, qi-stagnation constitution (QSC), QDC, and YIDC were PDC 2.49 (95CI%: 1.27-4.87), 2.03 (1.06–3.90), 1.78 (1.11–2.84), and 1.52 (1.09–2.10), respectively, while the OR for BC was 0.45 (0.30–0.66). Subgroup analyses revealed variations in TCM constitution distribution across regions and age groups, as well as difference associated with study quality.ConclusionPDC, YIDC, QDC, DHC, and BC are the most common TCM constitution types (prevalence ≥10%) observed in individuals with prediabetes. PDC, QDC, YIDC, and QSC may represent risk factors for prediabetes, whereas BC appears to be a protective factor. Further high-quality case–control and cohort studies are warranted to strengthen the evidence regarding the relationship between prediabetes and TCM constitution types.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024607164.